Acute focal bacterial nephritis characterized by acute encephalopathy with biphasic seizures and late reduced diffusion. Issue 11 (November 2018) - Yamaguchi, Hiroshi; Nagase, Hiroaki; Ito, Yusuke; Matsunoshita, Natsuki; Mizutani, Makoto; Matsushige, Takeshi; Ishida, Yusuke; Toyoshima, Daisaku; Kasai, Masashi; Kurosawa, Hiroshi; Maruyama, Azusa; Iijima, Kazumoto
Abstract: Acute focal bacterial nephritis (AFBN) is a localized bacterial infection of the kidney presenting as an inflammatory mass, and some patients show deterioration of clinical condition with neurological symptoms. Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is a syndrome that is characterized by biphasic seizures and impaired consciousness with reduced diffusion in the subcortical white matter on magnetic resonance imaging, typically observed between days 3 and 9 after clinical onset. Although AFBN sometimes causes neurological symptoms, no cases of AFBN with AESD have been reported, and no studies have presented the cytokine profiles of patients with a severe form of acute encephalopathy with AFBN. We report here a very rare case involving a 6-month-old boy who developed AFBN due to Enterococcus faecalis with both the clinical and radiological features of AESD. In our patient, serum interleukin (IL)-6, IL-10, and interferon (IFN)-γ levels markedly increased on admission, and on day 4, only IL-6 levels significantly increased in the cerebrospinal fluid (CSF). These results suggest that high serum cytokines are produced locally in response to AFBN and elevated IL-6 levels in CSF may have neuroprotective roles.